Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae) - Podeniene, Virginija; Nasevičiene, Nijole; Podenas, Sigitas (Zootaxa, 2019)
The egg-larvae of 890 individuals in 8 species belonging to long palped crane flies of the genus Tipula (Diptera: Tipulidae) were obtained from 17 gravid females captured in Lithuania in 2011–2012. Depending on the species, it took from four days to more than eleven weeks for the eggs to hatch. Of the four instars of larvae for crane flies, the second, third and the last instar larvae are very similar in morphology, while the first instar or egg-larva differs radically. Descriptions and illustrations of the external morphology, chaetotaxy of abdominal segments, characters of head capsules and last abdominal segments are given for the previously unknown first instar larvae of T. (Lunatipula) fascipennis, T. (Pterelachisus) irrorata, T. (P.) pabulina, T. (P.) pseudovariipennis, T. (Yamatotipula) pruinosa and poorly known T. (Beringotipula) unca, T. (L.) vernalis T. (Tipula) paludosa. The differences of the head capsule and last abdominal segment among the first instar larvae of these species are more obvious than in the last instar. Characters of the head capsule such as the shape of the teeth of the mandible, shape of the basal segment of the antenna and number of sensillae on it, shape of hypostomium, arrangement of sensory structures on the labrum and frons, all differ among egg-larvae of Tipula. Sclerotisation and the arrangement of setae on the spiracular field are unique for each studied Tipula species. This is the first study to use head capsule characters to distinguish the larvae of Tipula.